The antiplasmodium effects of a traditional South American remedy: Zanthoxylum chiloperone var. angustifolium against chloroquine resistant and chloroquine sensitive strains of Plasmodium falciparum (2011)
ABSTRACT: Zanthoxylum chiloperone var. angustifolium Engl., Rutaceae, is used medicine to treat fungal and protozoal infections in the central area of South America. Considering the increasing resistance of Plasmodium falciparum in malarial ridden areas, we explored the anti-plasmodial effects of three compounds isolated from Z. chiloperone. The pyranocoumarin transavicennol and the canthinone alkaloids, canthin-6-one and 5-methoxycanthin-6- one, were found to have IC50 on chloroquine/mefloquine resistant and sensitive strains of P. falciparum of 0.5-2.7, 2.0-5.3 and 5.1-10.4 μg/mL, respectively. Moreover, the formation of heme adducts by these compounds is described by a novel alternative method based on MS-CID methods. The alkylamide sanshool was also identified, for first time in this plant, in the dichloromethanic and ethanolic extracts and the extracts were found to be notably non-toxic and displayed good anti-plasmodial effects.